Electroplated Copper Metal Contacts on Perovskite Solar Cells. Issue 9 (2nd August 2021) - Hatt, Thibaud; Kabakli, Özde Ş.; Schulze, Patricia S. C.; Richter, Armin; Glunz, Stefan W.; Glatthaar, Markus; Goldschmidt, Jan Christoph; Bartsch, Jonas
Abstract : Electroplated copper contacts on small‐area single‐junction perovskite solar cells (PSCs) using an atomic layer deposited (ALD) Al2 O3 masking layer on ITO are demonstrated for the first time. The photoconversion efficiency of ≈11% after manufacturing the Cu contacts confirms that PSCs can survive the wet‐chemical plating process. From the successful realization of plated contact fingers, the creation of an electrical contact between the Cu electrode and the ITO on the FA0.75 Cs0.25 Pb(I0.8 Br0.2 )3 perovskite absorber is inferred. Furthermore, scanning electron microscopy (SEM) with energy‐dispersive X‐ray (EDX) analysis shows the formation of a compact interface between ITO and plated Cu. An additional plating approach, using self‐passivated aluminum as mask, allows to produce well‐defined 30 μm wide Cu contacts on the PSC. Such a plating process allows for plating a low‐resistive Cu grid simultaneously on both sides of a perovskite silicon heterojunction tandem solar cell with TCO, independent of substrate size. Abstract : Further large‐scale photovoltaic deployment mandates the reduction of scarce Ag, typically comprising the metallic contact of solar cells. Electrodeposited Cu contacts are demonstrated for the first time on single‐junction FA0.75 Cs0.25 Pb(I0.8 Br0.2 )3 perovskite solar cells (PSCs) using an atomic layer deposition (ALD) Al2 O3 masking layer on ITO. The stable photoconversion efficiency after Cu 2+ reduction confirms that PSCs can survive wet‐chemical plating process.